The role of PD-1/PD-L1 in overshooting osteoclastogenesis in periprosthetic joint infections - Yi Ren; Denise Jahn; Stefanie Donner; Clemens Gwinner; Weijie Du; Dimitrios L. Wagner; Serafeim Tsitsilonis; Carsten Perka; Georg Duda; Arne Kienzle (Communications Biology)
Abstract Periprosthetic joint infection (PJI) is a critical complication following arthroplasty, leading to increased prosthesis failure rates post-treatment. This study explores the role of PD-1/PD-L1 signaling in osteoclastogenesis associated with PJI. Peripheral blood, bone, and bone marrow of 65 patients (20 primary osteoarthritis, 21 PJI septic explantation, 24 PJI prosthesis reimplantation) were analyzed for their bone microstructure and cell composition. Immunocytochemistry, RT-qPCR, flow cytometry, bone resorption assay, ELISA, and RNA sequencing were performed to investigate the effects of PD-1 stimulation and blockade on osteoclast formation. PD-1 positive monocytes and sPD-L1 levels were elevated in PJI. Stimulation with PD-L1 enhanced osteoclastogenesis, while PD-1 inhibitor nivolumab reversed these effects. Impact of PD-1 and nivolumab was significantly more pronounced in PJI compared to the control. Our study suggests PD-1/PD-L1 signaling plays a significant role in PJI-related osteoclastogenesis. These findings highlight the potential of PD-1 inhibitors as a novel approach to manage this challenging clinical condition.